The Role of Personnel Management Supporting Telkom University's Excellent Accreditation Ratings - Muhtar, Zainal; Hanafiah, Hanafiah; Wiani, Ida Teja; Wahyudin, Wahyudin; Y, Maria Susana (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2022)
Human resources are a system driver that has a big influence on the goals of an organization. The functions of Higher Education include developing innovative, responsive, creative, skilled, competitive, and cooperative Academic Civitas through the implementation of Tridharma. To be able to carry out this function, a higher education organization requires human resources who have high competence. The purpose of this study is to describe the role of personnel management in supporting the best accreditation ranking of Telkom University. This study uses a qualitative method. The results of the study indicate that the nine management personnel that have been implemented by Telkom University have been in accordance with the main function of management. This is a manifestation of the implementation of a higher education system at Telkom University that has met national standards.